PENERAPAN ASI EKSKLUSIF 6 BULAN VERSUS PEMBERIAN MAKANAN PENDAMPING ASI DINI DI INDONESIA - Umniyati, Helwiah (Lembaga Penelitian Universitas YARSI, 2005)
The benefits of breastfeeding are well established, so that in 2001 WHO has revised global recommendation on exclusive breastfeeding that mothers should exclusively breastfeed their children until 6 months old (the old recommendation was previously 4 months). After that, to fulfill the babies need on nutrition, babies are given complementary feeding while breastfeed should be continued until 2 years. Six months exclusive breastfeeding will reduce infant morbidity and mortality in developing countries. In Indonesia, although exclusive breastfeeding for 6 month has been implemented by Ministry of Health, it is only 1% of the mothers exclusively breastfeed their babies for 6 months. In Vietnam, children who were exclusively breastfed for less than 3 months got diarrhoea earlier and the prevalence of diarrhoea was greater than babies who were breastfed for more than 3 months. Complementary feeding should be given when babies are 6 months old. In Indonesia, however complementary feeding have already been given when the babies are just 7 days old or less. The babies got formula, honey, water, sweet water, fruits, etc. Proportion of babies aged less than 1 month receiving commercial complementary feeding was 4 ? 5 %, increasing with the increase of age. Early complementary feeding will affect the baby's health.